ESTRATEGIAS DE DISEÑO PASIVO PARA EDIFICACIONES EN ALTURA EN LA CIUDAD DE MADRID: ENFOQUE EN EL CONFORT TÉRMICO Y LUMÍNICO - Simbaña Escobar, Patricio (2025)
In previous decades, the field of museography focused on presenting a chronological narrative of historical events, progressing from the simple to the complex, and emphasizing condensed, factual data. Public engagement was limited to a passive role, with visitors positioned as spectators who remained on the margins of pre-established and pre-interpreted content, thereby discouraging critical and individual thinking. However, this paradigm has shifted in recent decades, as contemporary museography has introduced new strategies in exhibition design. This discussion paper explores storytelling as a museographic tool to foster meaningful connections with audiences, stimulate inquiry and the pursuit of knowledge, and reinforce a sense of identity and community. Keywords: Museography, interiorism, culture, storytelling.